0.00035 mm2 on‐chip leakage sensing unit for various devices in 10 nm FinFET process. Issue 4 (1st February 2018) - Oh, G.‐G.; Lee, Y.‐W.; Lee, B.
Abstract : An efficient on‐chip leakage sensing unit is proposed, which is composed of four stages. Device under test (DUT) arrays include 16 types of transistors for leakage measurement. Threshold detector monitors the crossing point of inverter threshold causing the transition. Transition time is inversely proportional to the leakage current of the selected DUT. This time information of threshold detector is converted to voltage manner through the time‐to‐voltage converter with the diode stacked voltage generator. The generated voltage is transferred to voltage controlled oscillator (VCO) for frequency conversion which is the final output of leakage sensor. The proposed sensor provides leakage information of the various types of devices by using the same sub‐circuit within on‐chip. The prototype sensor occupies 0.00035 mm 2 area and consumes 1200 μW with eight DUT arrays within a chip. Experimental results show the well‐correlated frequency output with device leakage current.